2001
DOI: 10.1038/sj.ijo.0801918
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic pathways underlying the endocrine, autonomic, and behavioral effects of leptin

Abstract: Leptin affects body weight by decreasing food intake, activating the sympathetic nervous system and regulating neuroendocrine function. This type of regulation is a hallmark of hypothalamic control, which typically integrates autonomic, endocrine and behavioral responses. We have performed a series of experiments investigating hypothalamic pathways underlying these actions of leptin. We found that leptin activates neurons that coexpress pro-opiomelanocortin (POMC) and cocaine-and amphetamineregulated transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
107
0
7

Year Published

2003
2003
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(120 citation statements)
references
References 21 publications
6
107
0
7
Order By: Relevance
“…In the last 10 years, a series of genetic and pharmacological experiments have indicated that circulating factors, such as leptin and insulin, act via medial and ventral hypothalamic nuclei to modulate feeding and metabolism (Friedman and Halaas, 1998;Cowley et al, 2001;Elmquist, 2001). However, it is not clear how information (orexigenic or anorexigenic) travels outside of the hypothalamus to other brain nuclei.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last 10 years, a series of genetic and pharmacological experiments have indicated that circulating factors, such as leptin and insulin, act via medial and ventral hypothalamic nuclei to modulate feeding and metabolism (Friedman and Halaas, 1998;Cowley et al, 2001;Elmquist, 2001). However, it is not clear how information (orexigenic or anorexigenic) travels outside of the hypothalamus to other brain nuclei.…”
Section: Discussionmentioning
confidence: 99%
“…For example, neurons located in the arcuate nucleus of the hypothalamus express receptors for leptin, a key protein hormone produced in adipocytes. Although current models suggest that the arcuate nucleus communicates with second-order feeding centers, such as the paraventricular nucleus or lateral hypothalamus (LH) (Friedman and Halaas, 1998;Cowley et al, 2001;Elmquist, 2001), little is known about the mechanisms and pathways that convey information to extrahypothalamic sites.…”
Section: Introductionmentioning
confidence: 99%
“…This population has been repeatedly implicated in transneuronal tracing studies as a major source of the central presympathetic innervation of a host of peripheral tissues (Strack et al, 1989), as well as a prominent seat of neurons in a position to influence concurrently both cardiac and adrenal medullary activity, which have been considered as "command" neurons for the fight-orflight response (Jansen et al, 1995). Accordingly, functional studies have linked this projection to a range of cardiovascular, renal, and metabolic processes that may be considered as adaptive responses to acute stress (Elmquist, 2001;Benarroch et al, 2005;Coote, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, peripherally administered leptin prevented food-deprivation-induced decreases in circulating leptin (figure 2a,b; Keen-Rhinehart & Bartness 2008) and attenuated food-deprivationinduced increases in food hoarding, being most effective in hamsters with the lowest foraging effort requirement (figure 1c-e; Keen-Rhinehart & Bartness 2008). It is generally accepted that leptin penetrates into the brain to act centrally to affect ingestive behaviour (Elmquist 2001), although evidence of leptin receptors on vagal sensory nerves (Buyse et al 2001) suggests an additional means by which peripheral leptin could affect food intake (but ultimately acting centrally as well). Indeed, in our studies, leptin more effectively blocked food-deprivation-induced increases in food hoarding when given centrally, inhibiting fooddeprivation-induced increases in food hoarding up to 48 h post-injection regardless of foraging requirement (figure 3a -c; Keen-Rhinehart & Bartness 2008).…”
Section: Peripheral Physiological Factorsmentioning
confidence: 99%